Identifying novel biomarkers associated with bladder cancer treatment outcomes - Castaneda, Peris R.; Theodorescu, Dan; Rosser, Charles J.; Ahdoot, Michael (Frontiers in Oncology, 2023)
Bladder cancer is a complex disease with variable prognosis. Recent investigations into the molecular landscape of bladder cancer have revealed frequent genetic alterations and molecular subtypes with therapeutic implications. Consequently, a shift toward personalized treatment of bladder cancer is underway. To this end, several biomarkers have been developed and tested in their ability to predict response to treatment in patients with bladder cancer and potentially help direct therapy. We performed a search of recently published PubMed articles using terms “biomarker,” “bladder cancer,” and the respective treatment discussed (i.e., “neoadjuvant” or “BCG”). In this review, we summarize the latest studies on novel biomarkers in bladder cancer with a focus on those intended to improve risk stratification and treatment selection.